A fiskális transzparencia és a társadalmi elszámolási mátrix kiterjesztése - Czagány, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
Enhancing transparency is a highly current and important task in improving public finances. In the most general sense, fiscal transparency means, that those economic actors which use data on the state and changes of the government budget to build their decisions on should be able to acquire these data in the appropriate quantity, quality and structure. One fundamental transparency-problem is the demarcation of macroeconomic actors viz. the sectors of the economy. This study aims at contributing to the solution of this problem by extending the social accounting matrix compiled in accordance with the guidelines of the ESA and SNA.